Unmasking imposter syndrome: Prevalence and associations with demographic and academic factors among international students in Hungary - Emeke, Ojei Collins; Gebregergis, Werede Tareke; Csukonyi, Csilla (Journal of International Students, 2026)
Imposter syndrome is a psychological condition in which high-achieving individuals doubt their accomplishments despite objective evidence of their success. Its prevalence is increasingly becoming a major concern among university students. Although imposter syndrome affects both domestic and international students, prior research has predominantly focused on domestic populations. Therefore, this study examined the prevalence of imposter syndrome and its associations with demographic factors and academic performance among international students (N = 221). Data were analyzed using frequency distributions, t-tests, and correlations. Findings revealed that while most students (58.8%) reported low to moderate levels, a considerable proportion (41.2%) experienced frequent and intense imposter feelings. Among Asian students, imposter syndrome was significantly associated with gender, friendships with locals, and Hungarian language proficiency. For African students, it was negatively related to academic performance. These results underscore the prevalence of imposter phenomenon among international students and highlight the need for targeted interventions and support systems.